Ag[B(S2O7)2]: The First Transition Metal Borosulfate Featuring Disulfate Groups. Issue 11 (26th January 2021) - Netzsch, Philip; Höppe, Henning A.
Abstract: Hitherto, the structural diversity of transition metal borosulfates has been limited to B−O−S and B−O−B bridges. Ag[B(S2 O7 )2 ] represents the very first transition metal borosulfate featuring S−O−S bridges. The compound was synthesized solvothermally in oleum (65 % SO3 ) and crystallizes in a new structure type in P 21 / c (no. 14) with Z =4, a =950.7(4) pm, b =960.1(4) pm, c =1173.0(4) pm and β =98.350(11)°. The crystal structure comprises complex anions [B(S2 O7 )2 ] − – consisting of a central boron atom and two chelating disulfate groups – and charge balancing Ag + ions. Vibrational spectroscopy confirms the presence of S−O−S bridges. A thermal decomposition from Ag[B(S2 O7 )2 ] towards Ag[B(SO4 )2 ] was monitored by means of thermogravimetric analysis (TGA) and temperature programmed X‐ray diffraction (TPXRD). Abstract : Ag[B(S2 O7 )2 ] represents the very first precious metal borosulfate containing disulfate groups, i. e . S−O−S bridges, and thus further enriches the crystal chemistry of transition metal borosulfates. By thermal release of SO3 originating from the disulfate groups, the complex anions [B(S2 O7 )2 ] − condense to one‐dimensional chains in Ag[B(SO4 )2 ] containing solely B−O−S bridges.